Enabling Conditions for Consumer-Centric Business Models in the United Kingdom Energy Market - Hardy, Jeffrey; Mazur, Christoph (Frontiers in Energy Research, 2020)
To achieve ambitious United Kingdom decarbonization targets, consumers will need to engage with energy services more so than they have done to date. This engagement could be active or delegated, where in the latter consumers pass responsibility for engagement to a third party in return for ceding some control over decisions. To date, insight into the barriers to consumer adoption of future business models has been limited. To address this gap this study explored benefits, risks and enabling conditions using two extreme consumer-centric business models, third Party Control and Shared Economy. The approach yielded information from stakeholders on what would have to be true for one of the business models to dominate the market. The results show substantial agreement across the expert groups on five key issues that will need to be addressed in the near-term to enable energy business model innovation in the United Kingdom market. These are: 1) Create space to enable business model innovation; 2) Ensure smart devices and data are interoperable and secure; 3) Improve the service standards of energy businesses; 4) Ensure business models work for consumers in all situations; and 5) Implement targeted carbon regulation.